Исследование напряженного состояния горного массива вокруг выработки в зоне ее сопряжения с выработанным пространством лавы - Круковский, А.П. (Геотехническая механика, 2010)
Виконано чисельне моделювання напружено-деформованого стану порід навколо виро-
бок з арковою формою перерізу, що закріплено рамним та анкерно-рамним кріпленням, у зоні їх сполучення з лавою. Проведено порівняльний аналіз зміни розподілів напружень у цих
випадках. The numerical simulation of the stress-strain state of rocks around the workings of an arch
shape cross section, fixed frame and anchor-frame support in the area of their conjunction with the
goaf. A comparative analysis of changes in the distribution of stresses in these cases cases is carried
out.